Implementasi Pasal 365 Kitab Undang-Undang Hukum Pidana (KUHP) Tentang Pencurian Kekerasan - Prasetyo, Dandy Yudha; Faridah, Hana (Jurnal Ilmiah Wahana Pendidikan, 2024)
People are able to find other routes by taking because of economic concerns. Due to unfulfilled needs, inclusion in widespread communication - both print and electronic - shows vacillation in different types of robbery offenses. The thieves (fraudsters) may carry out their crimes in a variety of ways or according to their standard operating procedures, which change from one error to the next. The goal of this study is to ascertain how Article 365 of the Criminal Code (KUHP) pertaining to Violent Theft and criminal responsibility for perpetrators is implemented, as well as how Article 365 of the Criminal Code (KUHP) pertaining to Violent Theft is implemented. Legal analysis along with literature review is the methodology employed. The findings indicated that robbery committed with brutality was a property defect. In order for the stolen items to remain in the hands of the perpetrator and there to be still challenges in its application, the robbery's brutality has a point of planning or working with the theft or, on the other hand, assuming there is a possibility for the perpetrator to flee.